The Influence of Location, Service Quality, and Price Perception on Customer Satisfaction: The Mediating Role of Brand Image - Sibarani, Elfrida Dwiputri Roniuli; Silitonga, Parlagutan (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This research analyzes the influence of location, service quality, and price perception on customer satisfaction, with brand image as a mediating variable, in the context of Aston Hotel. The data in this study were collected using a questionnaire distribution with a purposive sampling technique, resulting in 300 respondents consisting of guests who used the service more than twice at the Aston Hotel. The hypotheses were tested using Structural Equation Modeling (SEM), applying a variance-based approach known as Partial Least Squares (PLS) through SmartPLS3 software. The results showed that price perception impacts brand image (t = 6,547; p = 0,000) and customer satisfaction (t = 4,432; p = 0,000). Additionally, brand image significantly influences customer satisfaction (t = 3,470; p = 0,001). In this study, location does not directly affect customer satisfaction (t = 0,677; p = 0,499). However, through brand image, location positively affects customer satisfaction (t = 2,804; p = 0.005). Conversely, service quality significantly affects customer satisfaction (t = 5,493; p = 0.000) but does not directly affect brand image (t = 1,798; p = 0.073). These results suggest important managerial implications, particularly the need for hotels to align pricing strategies with the perceived value of services and to enhance brand image through exceptional customer experiences. The finding emphasizes the crucial contribution of brand image in mediating the relationship that leads to greater customer satisfaction.